Effective Bat Houses for Florida - Holly K. Ober (EDIS)
WEC-246, an 8-page illustrated fact sheet by Holly K. Ober, describes how to attract bats to your property, select a location for a bat house, how to mount it, reasons bats might stay away, and concerns. Includes additional sources of information and bat house plans. Published by the UF Department of Wildlife Ecology and Conservation, August 2008.